The Escarpão Plateau (South of Portugal)—a study case of nested geosites from the aspiring Algarvensis Geopark - Veiga-Pires, Cristina (2024)
Flatfish species seem to require dietary taurine for normal growth and development. Although dietary taurine supplementation has been recommended for flatfish, little is known about the mechanisms of taurine absorption in the digestive tract of flatfish throughout ontogeny. This study described the cloning and ontogenetic expression of the taurine transporter (TauT) in the flatfish Senegalese sole (Solea senegalensis). Results showed a high similarity between TauT in Senegalese sole and other vertebrates, but a change in TauT amino acid sequences indicates that taurine transport may differ between mammals and fish, reptiles or birds. Moreover, results showed that Senegalese sole metamorphosis is an important developmental trigger to promote taurine transport in larvae, especially in muscle tissues, which may be important for larval growth. Results also indicated that the capacity to uptake dietary taurine in the digestive tract is already established in larvae at the onset of metamorphosis. In Senegalese sole juveniles, TauT expression was highest in brain, heart and eye. These are organs where taurine is usually found in high concentrations and is believed to play important biological roles. In the digestive tract of juveniles, TauT was more expressed in stomach and hindgut, indicating that dietary taurine is quickly absorbed when digestion begins and taurine endogenously used for bile salt conjugation may be recycled at the posterior end of the digestive tract. Therefore, these results suggest an enterohepatic recycling pathway for taurine in Senegalese sole, a process that may be important for maintenance of the taurine body levels in flatfish species.